Selenium nanoparticles modulate histone methylation via lysine methyltransferase activity and S-adenosylhomocysteine depletion - BENOIT TOUBHANS (Redox Biology, 2023)
At physiological levels, the trace element selenium plays a key role in redox reactions through the incorporation of selenocysteine in antioxidant enzymes. Selenium has also been evaluated as a potential anti-cancer agent, where selenium nanoparticles have proven effective, and are well tolerated in vivo at doses that are toxic as soluble Se. The use of such nanoparticles, coated with either serum albumin or the naturally occurring alkaline polysaccharide chitosan, also serves to enhance biocompatibility and bioavailability. Here we demonstrate a novel role for selenium in regulating histone methylation in ovarian cancer cell models treated with inorganic selenium nanoparticles coated with serum albumin or chitosan. As well as inducing thioredoxin reductase expression, ROS activity and cancer cell cytotoxicity, coated nanoparticles caused significant increases in histone methylation. Specifically, selenium nanoparticles triggered an increase in the methylation of histone 3 at lysines K9 and K27, histone marks involved in both the activation and repression of gene expression, thus suggesting a fundamental role for selenium in these epigenetic processes. This direct function was confirmed using chemical inhibitors of the histone lysine methyltransferases EZH2 (H3K27) and G9a/EHMT2 (H3K9), both of which blocked the effect of selenium on histone methylation. This novel role for selenium supports a distinct function in histone methylation that occurs due to a decrease in S-adenosylhomocysteine, an endogenous inhibitor of lysine methyltransferases, the metabolic product of methyl-group transfer from S-adenosylmethionine in the one-carbon metabolism pathway. These observations provide important new insights into the action of selenium nanoparticles. It is now important to consider both the classic antioxidant and novel histone methylation effects of this key redox element in its development in cancer therapy and other applications.